A Survey to Understand the experience of ChatGPT Usage among Engineering University Students in Bangladesh - Naher, Jibon; Maruf, Mizbaul Haque; Bakht, Syed Tamzid; Sadaf, Syed Samin (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study explores how university students in Bangladesh utilize ChatGPT, an AI-powered educational tool. Through a survey of 62 students of an engineering institution, the research uncovers that ChatGPT predominantly aids them in educational tasks, such as homework assistance and test preparation. While appreciated for its convenience, concerns exist among the students about accuracy, reliability, and potential overreliance. This study underscores the potential value of ChatGPT in education if used judiciously, highlighting the importance of striking a balance with conventional learning methods. It also advocates for the formulation of clear usage guidelines in educational institutions and recommends further research to understand the long-term effects on students' learning and academic performance.